On macrohedging problem in semimartingale markets - Abdelghani, Mohamed; Melnikov, Alexander (Frontiers in Applied Mathematics and Statistics, 2015)
Macrohedging is a hedging technique commonly used in practice. It allows one to find a hedging policy that offsets several underlying risk factors of a portfolio of assets as a whole. Here, we develop a macrohedging methodology in a general semimartingale market. We calculate the optimal macrohedge that achieves minimum risk, in a quadratic-variation sense, given a set of possible hedging instruments. We illustrate general macrohedging results by the Black-Scholes model.